EFFECT OF GROSS DOMESTIC PRODUCT, INFLATION, INTEREST RATE, PROFITABILITY AND CAPITAL ADEQUACY RATIO TO NON PERFORMING LOAN ON MIXED BANKS IN 2012-2015 - Purwohandoko, Purwohandoko (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2018)
Bank is a financial institution with the purpose of providing loans and services. Credit is the provision of money or product that is equated with money to make an agreement between the bank and the borrower where the borrower is obliged to fulfill its obligations within the period specified by the interest paid first. But in the process of lending to the public, the banks have problems such as credit risk, where the borrower is unable to repay the loan as agreed. So this raises the problem loans or bad credit. This study aims to determine the effect of economic factors, which uses variable Gross Domestic Product (GDP), inflation, and interest rates, as well as the internal bank uses variable profitability by proxy Return on Assets (ROA), and the Capital Adequacy Ratio (CAR ) against non-performing loans (NPLs). Data used in this study is taken from mixed banks year period 2012-2015. The analytical method used in this study is the linear multiple regression analysis. Variabel interest in this study is removed from the model because it does not pass the classic assumptions test. The research results are variable GDP negative effect on NPLs, the economy will increase the value of NPLs. CAR negative effect on NPLs, increasing the bank's capital will reduce the level of NPLs. ROA and inflation does not affect the NPL, any changes in these two variables do not affect the value of the NPL.